EXPERIENCE IN ELABORATING THE NATIONAL SYSTEM FOR ESTIMATING THE LAND SUITABILITY - V. A. Rozhkov (Бюллетень Почвенного института им. В.В. Докучаева, 2014)
Under discussion is the FAO algorithm modified to estimate the suitability of lands and soils for agricultural purposes using the definite LUI index (land unit index). The latter is calculated by rating of soil indices taken into complete account and accepted by FAO, USDA (USA) and the Ministry of Agriculture in the Russian Federation. The algorithm and proposed computer programs of interactive expert systems ((ADAPTER, LAND, PLANT) are universal and make it possible to use the indices for solving a number of intricate tasks in off-line regime.